INNOVATIVE APPROACHES TO DEVELOPING SAFETY STANDARDS FOR TRANSPORTING HAZARDOUS CHEMICALS: INTERNATIONAL EXPERIENCE AND APPLICATION IN THE UNITED STATES - Ковриженко, Тамара (SWorldJournal, 2025)
The article focuses on innovative approaches to shaping safety standards for transporting hazardous chemicals, taking into account international experience and their application in the United States of America. The purpose of the article is to examine inn